Impacts of Duty Belts and Load Placement on Police Officers: A Systematic Review - Berner, Nolan; Hunter, Daniel; Biilmann , Christopher; Canetti, Elisa F.D.; Schram, Ben; Dawes, Jay; Lockie, Robert; Orr, Robin M (NBP. Nauka, bezbednosti, policija, 2024)
Background: Law enforcement officers (LEO) wear duty belts to hold the specialised equipment required to complete their daily occupational tasks. The aim of this review was to identify, collect, and synthesize research investigating the impacts of duty belts and load placement on LEOs. Methods: A systematic review, registered with the Open Science Framework, was conducted following the Preferred Reporting Items for Systematic Reviews guidelines. Five databases were searched (PubMed, Embase, CINAHL, SPORTDiscus, and Web of Science) with identified studies considered against eligibility criteria. Included studies were critically appraised by two reviewers independently using the Joanna Briggs Institute checklist or the Mixed Method Appraisal Tool. Results: Ten studies (mean appraisal score = 79.8%; Kappa agreement = 0.73) informed the review revealing two main emerging themes; occupational impacts (task performance, vehicle duties, and weapon draw time), and movement impacts (balance, gait, and jump-based movements). Nine studies found duty belts and equipment loads, regardless of placement, negatively impacted LEO occupational tasks and movements in general. There were some differences in the nature of the impacts (e.g., areas of pressure with different systems). One study found no differences in performance be-tween hip versus thigh holsters. Conclusions: The evidence suggests that LEO duty belts, their attachments, and the loads imparted by their equipment have a negative impact on performance of occupational tasks as well as officer movement, increasing injury potential. There were some differences in impacts based on load placement warranting consideration and further research.
Keywords: law enforcement, load carriage, accoutrements belt, load bearing vest, duty loads, occupational health, back injury, injury prevention.